Kota ramah anak: konstelasi implementasi kebijakan perlindungan anak di kota Jambi - Riri Maria Fatriani; Dodi Al Vayed; Reza Amarta Prayoga (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This study aims to identify and analyze the constellation of implementation of Child Protection Policy in Jambi City. The theory of policy implementation by Merilee S. Grendle and the theory of preventive and repressive social control (social control) underlies this research. The research method used is a qualitative descriptive method that is empirical. Data processing techniques used by the author through the stages of data reduction, data presentation, and drawing conclusions. The results showed that the escalation of violence against children in Jambi has increased, especially neglect and physical violence. This is evidenced by an increase in cases from 2016 to 2018 reaching 52 cases. This case is dominated by triggers of financial problems and emotional disturbances. The implementation of child protection policies in Jambi City has been contained in the Jambi City Regional Regulation Number 05 of 2017, forming an integrative task force for the Jambi City child social welfare program.